National Trends of Hospitalizations in Cystic Fibrosis Highlight a Need for Pediatric to Adult Transition Clinics. Issue 5 (May 2021) - Ramsey, Mitchell L.; Lara, Luis F.; Gariepy, Cheryl E.; Abu-El-Haija, Maisam; Hart, Phil A.; Hinton, Alice; Kirkby, Stephen E.; Krishna, Somashekar G.; Li, Susan S.; Conwell, Darwin L.
Abstract : Objectives: We hypothesized that hospitalizations in cystic fibrosis (CF) would reflect the development of age-related comorbidities. Methods: A retrospective analysis was performed using the Nationwide Inpatient Sample (2002–2017). Hospitalizations for which the principal diagnosis was CF were analyzed regarding age at discharge and presence of comorbidities. Trends were assessed for significance using the Cochran-Armitage test. Results: The mean age of patients hospitalized for CF increased from 19.7 years in 2002 to 23.0 years in 2017 ( P = 0.017). Several comorbidities are more than 10 times more prevalent among adults as compared with children, including congestive heart failure, substance abuse, and chronic kidney disease ( P < 0.001). In addition, diabetes with chronic complications was more prevalent in adults than children (10.0% vs 3.9%; P < 0.001), as was hypertension (7.2% vs 1.3%; P < 0.001) and osteoporosis (10.2% vs 1.9%; P < 0.001). More than 65% of CF hospitalizations in 2017 were in individuals older than 18 years. Conclusions: Hospitalizations for adults with CF are increasing, and individuals with CF are developing age-related comorbidities. Providers equipped to manage the health care needs of adults need to be ready and able to care for this unique and growing patient population. Abstract : Supplemental digital content is available in the text.